2010
DOI: 10.1186/1471-230x-10-52
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-2 deficiency enhances non-alcoholic steatohepatitis

Abstract: BackgroundPreviously we reported that mice deficient in toll-like receptor 4 (TLR-4) signalling were protected from diet-induced non-alcoholic steatohepatitis (NASH). Another member of the toll-like receptor family, TLR-2, has been shown to play a role in lipid trafficking via uptake of diacylated lipoproteins. However, a role for TLR-2 in NASH has not been elucidated. The objectives of the current study were to examine the influence of dietary fat quality and TLR-2 on NASH pathogenesis.MethodsSteatohepatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Additionally, our data and that of others suggest that isocaloric diets with a greater content of omega-6 PUFAs can produce greater IR, result in a poorer TC/HDL-C ratio, and may even increase infl ammation ( 46,55 ), more so than an isocaloric diet composed of signifi cantly more SF. Meanwhile, others have shown that high consumption of omega-6 FAs has been associated with reduced infl ammation, a more favorable TC/HDL-C ratio ( 55 ), and no negative effects on infl ammatory markers ( 61,62 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, our data and that of others suggest that isocaloric diets with a greater content of omega-6 PUFAs can produce greater IR, result in a poorer TC/HDL-C ratio, and may even increase infl ammation ( 46,55 ), more so than an isocaloric diet composed of signifi cantly more SF. Meanwhile, others have shown that high consumption of omega-6 FAs has been associated with reduced infl ammation, a more favorable TC/HDL-C ratio ( 55 ), and no negative effects on infl ammatory markers ( 61,62 ).…”
Section: Discussionmentioning
confidence: 85%
“…al. ( 46 ) reported that a MCFA-rich diet more effectively attenuated nonalcoholic steatohepatitis and reduced hepatic TLR-4 expression versus a PUFA-rich diet. These convergent fi ndings may be explained by the inclination of lauric acid to be oxidized in vivo, thus limiting its ability to serve as a ligand for TLRs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…27 Mice deficient in TLR2 and TLR4 display attenuation in diet-induced hepatic steatosis and alcoholic liver injury. [48][49][50] Although this study did not thoroughly examine the role of specific TLRs in detail, the increased expression of multiple TLRs in Hfe À / À mice following ethanol and HFD suggests a possible role of iron in modulating TLR signaling in liver diseases. The mechanisms behind this remain unclear, but may involve LPS-independent pathways as there is currently no evidence that Hfe deficiency or iron overload affects hepatic responses to portal endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to wild-type mice, TLR2-deiciency animals are substantially protected from high-fat diet-induced adiposity, insulin resistance, hypercholesterolemia, and hepatic steatosis [39]. In contrast, increased hepatic inlammation and TNFmRN" expression were observed in TLR2-deiciency mice fed with MCDD [33,40]. The conlicting results of the role of TLR2 signaling in those studies could be due to diferent animal models used, diferent gut microbial ligands involved or compensation by other TLRs.…”
mentioning
confidence: 50%